Acoustic Bessel Vortex Beam by Quasi-Three-Dimensional Reflected Metasurfaces - Yin Wang (MDPI AG, 2021)
Vortex beams have a typical characteristic of orbital angular momentum, which provides a new degree of freedom for information processing in remote communication and a form of non-contact manipulation for trapping particles. In acoustics, vortex beams are generally observed on the surface of a metamaterial structure or in a waveguide with a hard boundary owing to the characteristic of easy diffusion in free space. The realization of an acoustic vortex beam with a long-distance propagation in free space still remains a challenge. To overcome this, we report a type of acoustic Bessel vortex (ABV) beam created by a quasi-three-dimensional reflected metasurface in free space based on phase modulation. By using the Bessel and vortex phase profiles, we can realize an ABV beam with the high performances of both Bessel and vortex beams, and its effective propagation distance is larger than 9.2λ in free space. Beyond that, we discuss the bandwidth and topological charge of the ABV beam in detail, and the fractional bandwidth can reach about 0.28. The proposed ABV beam has the advantages of a high-performance vortex, long-distance propagation, and broad bandwidth, which provide a new pathway for designing multifunctional vortex devices with promising applications.